A Community-Based Reading House Program to Enhance Reading and Writing Literacy among Elementary School Children in Nagari Gurun - Darti, Mila; Dasmi, Misa (Mangabdi: Journal of Community Engagement in Religion, Social, and Humanities, 2025)
Low levels of reading and writing literacy among children remain evident in Nagari Gurun, Jorong Luak Gadang, Sungai Tarab District, both in formal school learning activities and in everyday life. In response to this condition, the community service team designed and implemented a Reading House program as an effort to strengthen literacy skills among elementary school children. This program employed a descriptive qualitative approach and was conducted through three main stages: planning, implementation, and monitoring. The program was carried out over a three-month period and involved 50 children, consisting of 31 girls and 19 boys, ranging in age from under seven to over thirteen years old. Data were collected through observation, interviews, and documentation. The results indicate a notable improvement in children’s reading and writing abilities, as reflected in increased reading fluency, better comprehension of simple texts, and enhanced ability to write short, coherent sentences. These improvements were evidenced through observations of learning activities, mentoring records, and comparisons between participants’ initial and final literacy skills. In addition, the program successfully fostered children’s interest in reading and learning motivation through the provision of reading materials, guided learning sessions, educational games, and interactive discussions. Overall, the community-based Reading House program proved to be an effective educational strategy for improving basic literacy skills and fostering a more literate learning environment in Nagari Gurun, Jorong Luak Gadang.